Theoretical mapping of the barriers and enablers to having blood pressure checked among adults without a hypertension diagnosis: a systematic review and theoretical synthesis using behaviour change frameworks - McKinlay, Alison R.; Antonopoulou, Vivi; Schenk, Paulina M.; Lorencatto, Fabiana; Oliver, Emily J.; Vlaev, Ivo; Kelly, Michael P.; Sniehotta, Falko F.; Chater, Angel M. (Health psychology review, 2025)
Identifying influences on engagement with blood pressure (BP) checks can assist with intervention design for hypertension detection. This systematic review searched four databases (Embase, Emcare, MEDLINE and Web of Science) for papers published from 2015 to 2023 (PROSPERO ID: CRD42023398002). Eligible studies reported influences on BP checks in community or primary care settings. Data were coded and mapped using the Action, Actor, Context, Target, Time framework and Behaviour Change Wheel. Analysis of 18 studies generated eight themes: (1) ‘Difficult-to-use devices with no accessible information on how to use them' (2) ‘Lack of awareness about hypertension and BP checks', (3) ‘Stigma and disconnect with identity' (4) ‘Beliefs about the value of BP checks', (5) ‘Fear and uncertainty', (6) ‘Lack of appropriate and comfortable local services' (7) ‘Financial cost of engaging with BP check services' and (8) ‘Social contacts or health professional recommended a check'. Knowledge, identity, emotions, social contacts and environmental factors are key behavioural influences on adults’ engagement with BP checks. Potential intervention strategies include education on hypertension, addressing misconceptions about BP checks, increasing access to BP check services and harnessing the influence of social norms, social connections and trusted sources to improve engagement.